The Concept and Scope of Defamation (Fitnah) in Al-Quran Al-Kareem and Its Relation to Freedom of Speech in Malaysia - Abdul Samat Musa (AJBAS Publisher, 2024)
The issue of defamation is an issue that is so overwhelming that discussed by all walks of life. Al-Quran Al-Kareem also recorded this issue so thoroughly that it is mentioned more than eighty verses in total. In view of the importance of the issue of defamation which can influence the society, there are specific laws that have been enacted by the Parliament of Malaysia in ensuring the continuity of the enforcement of justice in the society through the concept of the rule of law which can be implemented accordingly. The discussions of this paper are mainly focused on the concept and scope of defamation according to Al-Quran Al-Kareem, As-Sunnah of the Prophet Muhammad (sallallahu ‘alaihi wasallam) and opinions of various scholars, and its relationship with the application of defamation laws in Malaysia. The findings from the research show that there is a close correlation on the importance and position of defamation in Islam and the Malaysian laws at large. A framework towards harmonizing the laws between Islamic and the Malaysian laws is a right step in identifying and resolving these issues more effectively.